2017
DOI: 10.1177/1179556517746646
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Mortality Among Newborns With Perinatal Asphyxia: A 4-Year Prospective Study of Newborns Delivered in Health Care Facilities in Enugu, South-East Nigeria

Abstract: Fatalities from perinatal asphyxia remain high in developing countries, and continually assessing its risk factors will help improve outcomes in these settings. We explored how some identified risk factors predict mortality in asphyxiated newborns, to assist clinicians in prioritizing interventions. This was a 4-year prospective study conducted at the Enugu State University Teaching Hospital, Enugu, Nigeria. All newborns who met the study criteria that were admitted to this facility in this period were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
20
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 18 publications
15
20
9
Order By: Relevance
“…The in-hospital case fatality rate for asphyxia in this study was 14.7% and about a third of these newborn infants died within 24 hours of admission, and this was despite early presentation to hospital. These asphyxia case fatality rates are similar to those previously described in studies from other low-resource settings [16][17]. In contrast, mortality prevalence was significantly higher in a previous North-western Nigerian study were rates of 25.5% were described [8].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The in-hospital case fatality rate for asphyxia in this study was 14.7% and about a third of these newborn infants died within 24 hours of admission, and this was despite early presentation to hospital. These asphyxia case fatality rates are similar to those previously described in studies from other low-resource settings [16][17]. In contrast, mortality prevalence was significantly higher in a previous North-western Nigerian study were rates of 25.5% were described [8].…”
Section: Discussionsupporting
confidence: 88%
“…We have conducted a prospective study and have used multivariable logistic regression to address possible confounders for risk estimates. This study thus improves on previous studies that have not adjusted for the effect of confounding or have been retrospective case analysis [16].…”
Section: Strengths and Limitationssupporting
confidence: 65%
“…However, this study suffers from some limitations, as e.g. more male than female neonates were incorporated in this study (Ekwochi et al 2017).…”
Section: Gender Differences In Severity Of Hiementioning
confidence: 99%
“…It is not strange in this setting for a parturient to first seek obstetric care during labour at non-orthodox facilities (traditional and spiritual birth homes) and thereafter to resort to orthodox facilities when emergencies occur or progress could not be made, by which time foetal compromise might have occurred. 16 Despite the pressure for early discharge from the nursery, babies should be screened for the risk of significant hyperbilirubinaemia using the various recommended tools (such as the normogram for plotting six-hour serum bilirubin level as a predictor of severe hyperbilirubinaemia within the first week of life). 29 Mothers should be taught how to check their babies for jaundice in bright light and be encouraged to seek care promptly when jaundice is detected.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] The odds of mortality among babies with these conditions have been variously reported to be higher among outborn babies. 6,7,[13][14][15] On a general note, studies in the developing world have suggested that babies delivered outside the hospital are at worse risk of complications such as hypoxic-ischaemic encephalopathy (HIE), 13,16 and acute bilirubin encephalopathy (ABE). 15,17 This higher tendency for complications occurs for various reasons ranging from inappropriate and ineffective home care, and delay in seeking effective care outside home, to seeking care at inappropriate places and non-availability of desired quality care, even at the appropriate health facilities.…”
Section: Introductionmentioning
confidence: 99%